Local application of biphosphonate as a biochemical barrier against bone graft resorption in mandibular reconstruction - Romzi Hanif; Muhammad Masykur Rahmat; Cahya Yustisia Hasan (Majalah Kedokteran Gigi Indonesia, 2019)
Mandibular reconstruction to restore functions and aesthetics after mandibular resection remains a major surgical challenge. This type of reconstruction using non-vascularized autogenous bone graft harvested from iliac bone has been popular given that this bone is numerous and donor site morbidity can be minimized, however, it is highly resorbable. Local application of bisphosphonate by immersing bone graft in biphosphonate manages to inhibit bone graft resorption prior to the formation of new bone to support the osteogenesis and osteointegration of bone grafts. This paper aimed at examining the positive results of iliac bone graft osteogenesis and osteointegration following local application of bisphosphonate in mandibular reconstruction. A 22-year-old female patient came with a complaint of painless right cheek mass that has swollen slowly since 2 years. Radiographic examination showed cloudy radiolucent images in the right mandibular corpus to the right mandibular ramus, while histopathological examination indicated ossifying fibroma. Patient underwent mandibular resection followed by iliac bone graft-based mandibular reconstruction. Bone graft was immersed with bisphosphonate (zoledronate acid 0.005 mg /ml) for 3 minutes, then rinsed with saline for 3 minutes, followed by fixing bone graft on the reconstruction plate. Postoperative follow up in the 36th week showed no signs of infection and dehiscence in the surgery site, and the radiographic examination indicated signs of osteogenesis and osteointegration of mandibular bone graft. Local application of biphosponate on bone graft promotes favorable results of osteogenesis and osteointegration in mandibular reconstruction.